2021
DOI: 10.3390/ijms222111781
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy for Colorectal Cancer: The Promise of Chimeric Antigen Receptor (CAR)-T Cells

Abstract: Colorectal cancer (CRC) is a global public health problem as it is the third most prevalent and the second most lethal cancer worldwide. Major efforts are underway to understand its molecular pathways as well as to define the tumour-associated antigens (TAAs) and tumour-specific antigens (TSAs) or neoantigens, in order to develop an effective treatment. Cell therapies are currently gaining importance, and more specifically chimeric antigen receptor (CAR)-T cell therapy, in which genetically modified T cells ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 102 publications
0
37
0
1
Order By: Relevance
“…Colorectal cancer (CRC) refers to colon and rectal epithelial tissue cancers that primarily affect the elderly and have a poor prognosis [ 153 ]. Various promising CAR T-cell-based therapeutic targets have been proposed in preclinical models for CRC, including CEA, EGFR, MUC1, NKG2DL, HER2, and CD133 with many therapeutic strategies [ 154 , 155 ]. Hedge et al published one of the first human studies utilizing first-generation retrovirally transduced CAR T-cells targeting tumor-associated glycoprotein (TAG)-72 in metastatic CRC.…”
Section: Car-modified Immune Cells In Solid Tumorsmentioning
confidence: 99%
“…Colorectal cancer (CRC) refers to colon and rectal epithelial tissue cancers that primarily affect the elderly and have a poor prognosis [ 153 ]. Various promising CAR T-cell-based therapeutic targets have been proposed in preclinical models for CRC, including CEA, EGFR, MUC1, NKG2DL, HER2, and CD133 with many therapeutic strategies [ 154 , 155 ]. Hedge et al published one of the first human studies utilizing first-generation retrovirally transduced CAR T-cells targeting tumor-associated glycoprotein (TAG)-72 in metastatic CRC.…”
Section: Car-modified Immune Cells In Solid Tumorsmentioning
confidence: 99%
“…Therefore, the chimeric antigen receptor is transferred in T cells, refined, and cryopreserved until patient administration. CAR-T therapy has shown dramatic results against hematologic and solid disorders, with a 70–90% response rate in relapsed/refractory conditions [ 1 , 7 , 8 , 11 ]. However, early trials suggested that the tremendous cytokine release might have profound clinical implications.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…With the introduction of this treatment, concerns about cardiotoxicity were progressively evaluated. From the mechanistic point of view, the cytokine cascade and signaling mechanisms leading to inflammatory activation are known [ 4 , 5 , 6 , 7 , 8 ], but a better understanding of the macroscopic counterpart is warranted. Cardiac events might result in prolonged hospitalization, life-threatening adverse events, or even death.…”
Section: Introductionmentioning
confidence: 99%
“…While classic chemotherapeutic treatment regimens predominantly target the proliferation and survival of tumor cells directly, more recent immunotherapeutic approaches instead aim at supporting anticancer immunity by modulating the tumor microenvironment. Thus, the principle of immunotherapy is primarily to increase the number of tumor-infiltrating and tumor antigen-specific cytotoxic T lymphocytes (e.g., by adaptive cell transfer [ 18 , 19 ] or by optimized recruitment of systemic effector cells) and to increase their cytolytic activity (e.g., by checkpoint inhibitors [ 11 ] or by inhibition of immunosuppressive components). However, a large proportion of CRC patients show only a rather disappointing response to monotherapy with clinically established PD-1 checkpoint inhibitors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%